Design and Evaluation of Diltiazem Controlled Release Tablets Employing Calcium Starch - Chowdary, K.P.R.; Tripura Sundari, P.; Neelima, N. (Asian Journal of Chemistry, 2010)
The objective of the present investigation is to synthesize calcium starch, a new starch based polymer and to evaluate its application in controlled release and in the design of diltiazem controlled release tablets. Calcium starch polymer was synthesized by gelatinization of starch in the presence of sodium hydroxide and cross linking by treatment with calcium chloride. Matrix tablets each containing 90 mg of diltiazem hydrochloride were formulated employing calcium starch polymer in different proportions of drug and polymer and the tablets were evaluated. Diltiazem release from the formulated tablets was slow and spread over 24 h and depended on per cent polymer in the tablet. Fickian diffusion was the drug release mechanism from the formulated tablets. Diltiazem release from matrix tablets F3 formulated employing 15 % calcium starch and F4 formulated employing 20 % calcium starch were similar to that from dilzem SR and DTM 90 SR tablets respectively. Calcium starch polymer was found suitable for the design of oral controlled release tablets of diltiazem.